Implementación de tecnología de telefonía sobre ip en tvpacific - Bohórquez Mite, Santos Javier (2010)
This thesis seminar provides the problem statement and its solution in TV-PACIFIC company via VoIP technology. The company has the service of the CNT and cellular telephony, which is the product of a monthly financial cost while noting that the company has not adhered to the high costs of communication. To carry out the project, it has been divided into two parts. The first is to propose and justify the investment of the necessary equipment, and the period of payback, the second part describes a brief explanation of VoIP telephony in the optimization of voice, main functions and advantages as: -The possibility of low-cost communication within the company and branches. -Improving the quality of voice, which makes the VoIP telephony gateway to new services. This solution has been considered indispensable for the entire company with a vision for grow